2015
DOI: 10.1073/pnas.1519696112
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling binding of substrate CO from turnover by vanadium nitrogenase

Abstract: Biocatalysis by nitrogenase, particularly the reduction of N 2 and CO by this enzyme, has tremendous significance in environmentand energy-related areas. Elucidation of the detailed mechanism of nitrogenase has been hampered by the inability to trap substrates or intermediates in a well-defined state. Here, we report the capture of substrate CO on the resting-state vanadium-nitrogenase in a catalytically competent conformation. The close resemblance of this active CO-bound conformation to the recently describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(111 citation statements)
references
References 25 publications
3
100
1
7
Order By: Relevance
“…The CO-bound M-and V-clusters displayed EPR signals with strikingly similar line shapes (Figure 8 c,d), [52] thus suggesting a close resemblance between the two CO-bound conformations (Figure 8 a,b). [52] However, while the "inhibited" state of the CO-bound M-cluster was hardly capable of turnover, the CO-bound V-cluster was catalytically competent and, thus, represented a substratebound state of nitrogenase. GC-MS analysis demonstrated that 13 CO could be preloaded onto the V-cluster and subsequently turned over into hydrocarbon products.…”
Section: A Central Role Of the Interstitial Carbide In C à C Couplingmentioning
confidence: 84%
See 3 more Smart Citations
“…The CO-bound M-and V-clusters displayed EPR signals with strikingly similar line shapes (Figure 8 c,d), [52] thus suggesting a close resemblance between the two CO-bound conformations (Figure 8 a,b). [52] However, while the "inhibited" state of the CO-bound M-cluster was hardly capable of turnover, the CO-bound V-cluster was catalytically competent and, thus, represented a substratebound state of nitrogenase. GC-MS analysis demonstrated that 13 CO could be preloaded onto the V-cluster and subsequently turned over into hydrocarbon products.…”
Section: A Central Role Of the Interstitial Carbide In C à C Couplingmentioning
confidence: 84%
“…. PDB entry 4TKV, [54] XAS/EXAFS, [51] and XES [52] data were used to generate these models. Atoms are colored as described in Figure 1 b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is a high degree of sequence identity between the MoFe protein and the VFe protein, which centers around the residues that are either ligated to or in the surroundings of the P-cluster and the cofactor [5,22]. The P-cluster of the VFe protein has long been thought to closely resemble the P-cluster of the MoFe protein in structure, but the recent characterization of the A. vinelandii VFe protein suggested otherwise [22,92]. The EPR data of the dithionite-reduced and IDS-oxidized forms of the VFe protein strongly indicate that the electronic properties of the P-cluster in the VFe protein are quite different than those of its counterpart in the MoFe protein [92].…”
Section: The Vfe Proteinmentioning
confidence: 99%